Analisis Dampak Covid 19 Dalam Peningkatan Gadai Emas Di Pegadaian Syariah Sibuhuan - Yudika L.K Rangkuti (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
The Covid-19 situation is causing problems for the world economy. In this case, sharia pawnshops have gold pawn products that can help the economy. Especially for customers in quickly addressing needs amidst the Covid-19 pandemic. This general research aims to find out the description and forms of efforts made by the Sibuhuan sharia pawnshop to help customers who pawned gold during the Covid-19 pandemic. This type of research is field research, while the nature of the research is qualitative descriptive. This research uses a normative and sociological approach. The data collection techniques are based on interviews and documentation. The data sources for this research come from primary data and secondary data. The results of the research show that the impact of Covid-19 on gold pawning products at the Sibuhuan sharia pawnshop has resulted in many customers pawning gold. However, during this pandemic there are many customers who cannot forgive the gold pawn. The efforts made by sharia pawnshops in the midst of the Covid-19 pandemic are by providing relief such as 0.5% ujrah fees to customers who have businesses, limiting operational hours to 09.00-13.00 and making it easier for customers to use the e-mas application.